KEUNGGULAN KOMPARATIF DAN DAMPAK KEBIJAKAN PEMERINTAH PADA PENGEMBANGAN PRODUKSI JAGUNG DI BENGKULU - ISADIKIN, IKIN (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 2, No. 1 Februari 2002, 2012)
The objective of this study was to analyze comparative advantage and the impact of government policy on corn production in Bengkulu. Primary and secondary data were collected by interviewing corn farmer, traders, and marketing institutional on October 1996. The data were analyzed by using Policy Analysis Matrix (PAM). The result show that Bengkulu corn production have relatively high comparative advantage as reflected by DRCR value of 0.5814. The impact of goverment policy gaves disinsentif to develop corn farmers, as to reflected by the value of NPCI=1.1704, NPCO=0.859, and EPC=0.833. To increase the efficiency, the government need to deregulate input (fertilizer) subsidy so that no input price differences between food crop sector and estate crop sector.
Keywords: Comparative Advantage, Government Policy, Corn Production.